Primary adenocarcinoma of the base of tongue: a rare case - Eskiizmir, Görkem; Özgür, Erdoğan; Tanyeri, Gökçe; Ayhan, Semin (ENT Updates, 2014)
Head and neck cancers are the sixth most common type of cancer in world; and of these, less than 10% are oropharyngeal cancers. The most common malignant tumor of oropharynx, even though it is accepted as a part of digestive system, is squamous cell carcinoma. On the other hand, adenocarcinoma, a common histopathological type for digestive system, is very rarely reported at base of tongue. Therefore, this article was aimed to present a 72-year-old male patient with a primary adenocarcinoma of the base of tongue and discuss the clinical presentation, radiological evaluation, histopathological examination, treatment modalities and prognosis with the literature.